Keabsahan Akta Autentik yang Mengandung Unsur Tindak Pidana Pemalsuan - Debby Dwi Arlingga (Universitas Islam Indonesia, 2017)
Notary deed is the perfect, strongest, and most complete proof of evidence, thus not only guaranteeing legal certainty but also avoiding disputes. In practice, however, disputes often arise due to the existence of a notary deed. The notary can be liable for his action in making authentic deeds that are not in accordance with the applied provisions or are carried out against the law. This study has 2 formulations of the problem, first, how is the validity of the deed made before a notary containing fraudulent acts according to the Decision of Supreme Court Number 1003 K/PID/2015, and second, how is the notary's liability for the notarial deed containing fraud. The method in this study is normative legal research. The results show that, first, based on the Decision of Supreme Court Number 1003 K/PID/2015 in conjunction with the decision of Pekanbaru District Court Number 247/Pdt.G/2016/PN.Pbr, the Notary Deed No. 149 dated March 30, 2011 is declared valid and valuable before the law, but in terms of the strength of evidence, it is degraded from authentic deed to private deed for violating Article 48, 49, 50, and 51 of Law on Notary concerning Investigators. Second, the notary's legal duty for the deed containing fraud includes criminal, civil, and administrative liabilities.Keywords: Authentic deed; fraud; notary